Keefektifan strategi konflik kognitif ditinjau dari kemampuan berpikir kritis - Inggrid Marlissa; Kamariah Kamariah (STKIP PGRI Banjarmasin, 2018)
The purpose of this study was to describe the effectiveness of cognitive conflict strategy learning in terms of critical thinking skills. This study was a experimental research whose population consisted of all 10thgraders in State Senior High School 2 of Merauke which includes six classes. Out of the six classes, one groups of students was randomly selected to class X MIPA 1. The data collecting techniques were a test whereas the instrument used to the collect the data consisted of critical thinking skills test. To see the effectiveness of cognitive conflict strategy learning using univariate tests. The univariate test used is one sample t test. The results of the study, using significance level 5%, showed that the cognitive conflict strategy learning is effective in terms of critical thinking skills and the level of critical thinking ability is in the medium category.